Occupied Territory: Policing Black Chicago from Red Summer to Black Power - Balto, Simon (Justice, Power, and Politics Ser., 2019)
Cover -- Half Title -- Title -- Copyright -- Dedication -- Contents -- Abbreviations -- Introduction: Overpoliced and Underprotected in America -- Prologue: The Promised Land and the Devil's Sanctum: The Risings of the Chicago Police Department and Black Chicago -- 1. Negro Distrust of the Police Increased: Migration, Prohibition, and Regime-Building in the 1920s -- 2. You Can't Shoot All of Us: Radical Politics, Machine Politics, and Law and Order in the Great Depression -- 3. Whose Police?: Race, Privilege, and Policing in Postwar Chicago -- 4. The Law Has a Bad Opinion of Me: Chicago's Punitive Turn -- 5. Occupied Territory: Reform and Racialization -- 6. Shoot to Kill: Rebellion and Retrenchment in Post-Civil Rights Chicago -- 7. Do You Consider Revolution to Be a Crime?: Fighting for Police Reform -- Epilogue: Attending to the Living -- Acknowledgments -- Notes -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W -- X -- Y.